Relationship between Total Quality Management principles and Culture of Teaching and Learning in Iranian secondary schools - Pour Rajab, Masoumeh (2013)
The present study was an attempt to explore relationship between the Total Quality Management (TQM) principles and Culture of Teaching and Learning (COTL) in 40 secondary schools in Lorestan province, located in west part of Iran. The study was also designed to determine the level of TQM and COTL in secondary schools. The researcher used a survey questionnaire to measure the variables among secondary school educators (n=320) and students (n=400) in Iran. Data were analyzed using descriptive statistics, Analysis of Variance (ANOVA), independent sample t-test,Pearson correlation, and multiple regressions. The results of this study showed that despite great effort made to implement TQM in Iranian secondary schools, the level of TQM and COTL is still at medium level based on students’ perception, but for principals’ and teachers’ perception, it is already at a high level. The level of TQM and level of COTL have a parallel relationship for principals, teachers and students,which mean by increasing in the level of TQM, the level of COTL will increase. The results also show that there is a strong relationship between character of role players (teachers, students, and parents) and COTL, and this means that teachers, students and parents have positive influence in improving the level of COTL. The strong relationship between character traits of role players and COTL showed that role players can improve the level of COTL. The study also finds that confidence in the status quo, lack of abilities to change, lack of communication, and lack of commitment as the factors of resistance to the implementation of TQM in schools. These major barriers to the implementation of TQM must be addressed by the educational advocators. The study proposed several potential recommendations to the Iranian Ministry of Education to overcome these barriers, and upgrade the level of Total Quality Management and Culture of Teaching and Learning in schools.